Efficacy and complications of blocking screws fixation in the treatment of lower limb long bone fracture: a meta-analysis - Jin, Zhaoguo; Wang, Ding (Frontiers in Surgery, 2025)
BackgroundLong bone fractures, especially in the lower limbs, are highly prevalent in orthopedic practice. These fractures can significantly impair patients' mobility and quality of life. Intramedullary nails are a mainstay treatment, offering reliable fracture fixation. However, the addition of blocking screws has introduced an element of uncertainty regarding surgical outcomes. This meta-analysis evaluated the efficacy and complications of blocking screw fixation for lower limb long bone fractures (LLLBF).MethodsA comprehensive and systematic search was conducted across eight databases, namely the Cochrane Library, PubMed, EMbase, Web of Science, CNKI, China Biomedical Literature Database (CBM), VIP, and WanFang, to identify relevant controlled trials. Before data analysis, the quality of each study was rigorously assessed. Subsequently, the data were analyzed using the Review Manager 5.3 (RevMan 5.3) software to ensure a reliable and accurate synthesis of the evidence.ResultsA total of 15 studies were incorporated into the analysis. Compared with the control group, the experimental group demonstrated a significantly shorter fracture healing time (standardized mean difference, SMD = −2.18; 95% confidence interval, CI: −3.17 to −1.20; P < 0.001), suggesting a substantial effect in favor of the intervention. Additionally, the experimental group had a longer operation time (SMD = 15.81, 95% CI: 4.28, 27.34, P = 0.007), less intraoperative bleeding (SMD = −75.60, 95% CI: −127.93, −23.27, P = 0.005), and fewer complications (odds ratio, OR = 0.51, 95% CI: 0.31, 0.84, P = 0.008). However, no significant difference was observed in the fracture healing rates between the two groups (OR = 1.09, 95% CI: 0.98, 1.20, P = 0.098).ConclusionThe findings of this study suggest that the use of intramedullary nails in conjunction with blocking screws could potentially be an effective treatment option for patients with lower limb long bone fractures. However, to confirm this efficacy, additional high - quality research, preferably well-designed randomized controlled trials with large sample sizes and long-term follow - up, is warranted.